Feasibility of lowering soybean planting density without compromising nitrogen fixation and yield - De Luca, Marcos Javier; Nogueira, Marco Antonio; Hungria, Mariangela (American Society of Agronomy, 2019)
Adjusting soybean [Glycine max (L.) Merrill] density can be critical to reduce inter-plant competition for water, nutrients, and sunlight, and to increase intercepted radiation, photosynthesis, and biomass production. The objective of this study was to evaluate the effects of soybean-population density on soybean nodulation, plant nutrient status, yield, and grain quality. Three field experiments were performed in southern Brazil with soybean cultivar BRS 284, of indeterminate growth type and maturity group 6.6, at 80,000 and 320,000 plants ha–1. For N supply plants were dependent either largely on biological fixation of atmospheric N—with a naturalized population of Bradyrhizobium or inoculated with Bradyrhizobium japonicum strain CNPSo 2050—or largely on N fertilizer—200 kg N ha–1, split-applied at sowing and R1 growth stage. The lower plant density resulted in increased nodulation parameters (number and mass), but plant nutritional status—evaluated by the diagnosis and recommendation integrated system (DRIS) method—in general was not affected. Seed oil content increased by 3.4%, but protein decreased by 4.5% at the lower plant density. The N source affected nodulation, but not nutritional status or grain yield. Although plant density was reduced by 75%, yield decreased by 16% during only one of the three cropping seasons. These results indicate a high plasticity of soybean to adapt photosynthesis and N fixation to different plant densities. Furthermore, planting at the lower density has the advantages of lower input costs and less susceptibility to environmental and plant nutritional stresses.